2021
DOI: 10.1007/s43545-021-00178-7
|View full text |Cite
|
Sign up to set email alerts
|

Status and utilization of child health and nutritional services among low-income urban households in Bangladesh

Abstract: The main aim of this study is to report the prevalence of Diarrhoea, Acute Respiratory Symptoms (ARS), and malnutrition in Bangladeshi among the low-income urban households' under-five children; and explore the health and nutritional services use and determine service gaps. The study used a quantitative research approach where a social survey was employed to collect data from 378 household heads (non-slum 228 and slum 152) through a structured interview method in Zone 5 (Kashimpur and Konabari) of the Gazipur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The low‐income urban community is an inordinate feature in Bangladesh. Unplanned urbanization is one of the important factors that lead to an extremely densely and poor living circumstances such as consumption of low‐quality food and poor housing, water, and sanitation conditions (Islam & Hamiduzzaman, 2021; Mottaleb et al, 2018; Khalequzzaman et al, 2017; Cameron, 2017). These disadvantages and risk factors are the main causes of malnutrition and sickness in the children and mothers (Islam et al, 2018; Ahsan et al, 2017; Kamal et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The low‐income urban community is an inordinate feature in Bangladesh. Unplanned urbanization is one of the important factors that lead to an extremely densely and poor living circumstances such as consumption of low‐quality food and poor housing, water, and sanitation conditions (Islam & Hamiduzzaman, 2021; Mottaleb et al, 2018; Khalequzzaman et al, 2017; Cameron, 2017). These disadvantages and risk factors are the main causes of malnutrition and sickness in the children and mothers (Islam et al, 2018; Ahsan et al, 2017; Kamal et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These disadvantages and risk factors are the main causes of malnutrition and sickness in the children and mothers (Islam et al, 2018; Ahsan et al, 2017; Kamal et al, 2015). Islam and Hamiduzzaman (2021) found that poor socioeconomic conditions and healthcare‐seeking behaviors are the main influences for diarrhea, ARS, and malnutrition. They further argued that there are some services in the community; they could not afford these services even if they were aware of them as they have to be paid for.…”
Section: Literature Reviewmentioning
confidence: 99%